DUAL-CHANNEL OPTICAL SMOKE DETECTOR - A. I. Kitsak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The optical scheme of smoke fire detector based on the laser source and which allows to realize method used in linear smoke detectors along with the traditional fire detection method for point smoke fire detectors (after intensity level of emission scattered by particles of smoke) is offered. Monitoring of the environment state by two independent channels increases the sensitivity of the detector and fire detection reliability. The conditions which provide high sensitivity of «linear» channel of smoke detection with low optical base were found. Model experiments to detect the smoke by experimental model of developed optical scheme of smoke fire detector are conducted.